The Role of the Plant Antioxidant System in Drought Tolerance - Miriam Laxa; Michael Liebthal; Wilena Telman; Kamel Chibani; Karl-Josef Dietz (MDPI AG, 2019)
Water deficiency compromises plant performance and yield in many habitats and in agriculture. In addition to survival of the acute drought stress period which depends on plant-genotype-specific characteristics, stress intensity and duration, also the speed and efficiency of recovery determine plant performance. Drought-induced deregulation of metabolism enhances generation of reactive oxygen species (ROS) and reactive nitrogen species (RNS) which in turn affect the redox regulatory state of the cell. Strong correlative and analytical evidence assigns a major role in drought tolerance to the redox regulatory and antioxidant system. This review compiles current knowledge on the response and function of superoxide, hydrogen peroxide and nitric oxide under drought stress in various species and drought stress regimes. The meta-analysis of reported changes in transcript and protein amounts, and activities of components of the antioxidant and redox network support the tentative conclusion that drought tolerance is more tightly linked to up-regulated ascorbate-dependent antioxidant activity than to the response of the thiol-redox regulatory network. The significance of the antioxidant system in surviving severe phases of dehydration is further supported by the strong antioxidant system usually encountered in resurrection plants.